A new species of the genus Bryodemella (s. str.) Yin, 1982 from China (Orthoptera: Acridoidea: Oedipodidae) - Zhang, Yu-Long; Zhi, Yong-Chao; Zhang, Dao-Chuan (Zootaxa, 2018)
A new species (i.e. Bryodemella (s. str.) rufifemura sp. nov. from China is described in this paper. It is similar to Bryodemella (s. str.) diamesum (Bei-Bienko, 1930), but differs from the latter by red inner side of hind femur, median keel of pronotum indistinct in metazoan, and vertical diameter of eye shorter than subocular groove in female. The type specimens are deposited in the Museum of Hebei University (MHU), China.